“Evaluation Of Langerhans Cells Using Cd1a In Oral Submucous Fibrosis: An Immunohistochemical Study” - Dr.Sourab Kumar; Dr.Abhishek Jadhav; Dr. Sejal Vijay Palve; Dr. Nisha Kumari Jaiswal; Dr. Saniya Subir Puthanpurakkal; Dr. Priyanka Anil Patil (Revista Electronica de Veterinaria, 2024)
The burden of cancer is still increasing worldwide despite advances for diagnosis and treatment. Epidemiological studies have shown that many cancers may be avoidable. It is widely held that 80–90% of human cancers may be attributable to environmental and lifestyle factors such as tobacco, alcohol and dietary habits. It was estimated that in the year 2000, worldwide over 10 million new cases of cancer occurred (approximately 5.3 million men and 4.7 million women) and over 6 million people died from cancers. This study aims to evaluate the presence of langerhans cells in various histological stages of OSMF using CD1a antibody, which has been suggested as the most reliable marker of langerhans cells differentiation & to determine whether alterations in the number of LCs impairs oral mucosal immunologic protection against mutagens such as areca nut (betel quid), tobacco constituents, which might play a role in oral epithelial dysplasia& oral squamous cell carcinoma.